Effect of carbon partition in the reverted austenite of supermartensitic stainless steel. (3rd May 2019) - Zhang, Yiwei; Zhong, Yuguo; Lv, Chuantao; Tan, Liwen; Yuan, Xiaomin; Li, Shengzhi
Abstract: In this study, the reverted austenite transformation from martensite and the distribution of carbon element during tempering process in supermartensitic stainless steel have been investigated by x-ray diffraction analysis with whole pattern fitting refinement and electron backscattered diffraction (EBSD). The results revealed that the microstructure consists mainly of tempered martensite and reverted austenite. The martensite matrix has high density dislocation and the misorientation angles range of 0°–60° in the stucture, while the reverted austenites nucleate and precipitate at sub-block boundaries and prior grain austenite boudndaries. With the tempering temperature increasing, the amount of reverted austenite increases first and then decreases, which is strongly depended on the tempering temperature. The carbon element dissolved in the reverted austenite has an opposite tendency due to the difference of carbon element partitioning. At the same time, the hardness results have the same trend. It manifested that reverted austenite contents have an effect on the mechanical properties. The amount of carbon enrichment in the reverted austenite is considered to be one of the main factors.